Performance vehicle dynamics : engineering and applications - Balkwill, James (Elsevier Science, 2017)
Performance Vehicle Dynamics: Engineering and Applications offers an accessible treatment of the complex material needed to achieve level seven learning outcomes in the field. Users will gain a complete, structured understanding that enables the preparation of useful models for characterization and optimization of performance using the same Automotive or Motorsport industry techniques and approaches. As the approach to vehicle dynamics has changed over time, largely due to advances in computing power, the subject has, in practice, always been computer intensive, but this use has changed, with modeling of relatively complex vehicle dynamics topics now even possible on a PC.